Delivering Community Emergency Medicine during the COVID-19 pandemic: the Physician Response Unit. Issue 5 (21st April 2021) - Carden, Rich; Leaning, Bill; Joy, Tony
Abstract : The COVID-19 pandemic has presented significant challenges to services providing emergency care, in both the community and hospital setting. The Physician Response Unit (PRU) is a Community Emergency Medicine model, working closely with community, hospital and pre-hospital services. In response to the pandemic, the PRU has been able to rapidly introduce novel pathways designed to support local emergency departments (EDs) and local emergency patients. The pathways are (1) supporting discharge from acute medical and older people's services wards into the community; (2) supporting acute oncology services; (3) supporting EDs; (4) supporting palliative care services. Establishing these pathways have facilitated a number of vulnerable patients to access patient-focussed and holistic definitive emergency care. The pathways have also allowed EDs to safely discharge patients to the community, and also mitigate some of the problems associated with trying to maintain isolation for vulnerable patients within the ED. Community Emergency Medicine models are able to reduce ED attendances and hospital admissions, and hence risk of crowding, as well as reducing nosocomial risks for patients who can have high-quality emergency care brought to them. This model may also provide various alternative solutions in the delivery of safe emergency care in the postpandemic healthcare landscape.